Associations of NEUROD2 polymorphisms and change of cognitive dysfunctions in schizophrenia and schizoaffective disorder after eight weeks of antipsychotic treatment. Issue 4 (4th July 2017) - Spellmann, Ilja; Riedel, Michael; Städtler, Julia; Zill, Peter; Obermeier, Michael; Cerovecki, Anja; Dehning, Sandra; Schennach, Rebecca; Epple, Maria; Opgen-Rhein, Markus; Müller, Norbert; Bondy, Brigitta; et al.
ABSTRACT: Introduction: NEUROD2 is a neurospecific helix–loop–helix transcription factor which has an impact on the regulation of glutamatergic and GABAergic genes. We investigated an association of NEUROD2 with neurocognitive dysfunctions in schizophrenia and schizoaffective disorder patients before and during treatment with different second-generation antipsychotics. Methods: Patients were genotyped for four different polymorphisms of the NEUROD2 gene ((rs9889354(A/G), rs1877032(C/T), rs12453682(C/T) and rs11078918(C/G)). Cognitive function was assessed at baseline and week 8. Results of individual neuropsychological tests were assigned to six cognitive domains (reaction time and quality; executive function; working, verbal and visual memory) and a general cognitive index. Results: 167 patients were included in the study. The NEUROD2 exonic polymorphism rs11078918 showed significant associations with verbal memory and executive functions, whereas the NEUROD2 polymorphism rs12453682 was significantly associated with working and verbal memory, executive functions and with a cognitive index. Significant associations were found at baseline and after eight weeks. Moreover, significant associations between the change in neuropsychological test results during antipsychotic treatment and the NEUROD2 polymorphisms rs11078918 and rs12453682 were observed. Conclusions: Our findings suggest that the NEUROD2 gene could play a role in the pathophysiology of neurocognitive dysfunctions as well as in the change of cognitive symptoms under antipsychotic treatment in schizophrenia and schizoaffective disorder.